The national question, monarchism and the state in the political views of the Russian emigrant Sergei Prokopovich - Kuznetsova, Olga (Études sur la Région Méditerranéenne, 2020)
Sergei Prokopovich was a moderate socialist and he held the post of minister of the coalition Provisional Government of Russia in 1917. In 1922 he was obliged to emigrate first to Berlin, and then to Prague. In Prague, he organized the Economic Cabinet (1924–1939), a well-known scientific center for the study of Soviet Russia.Unlike a significant part of the Russian emigration, Sergei Prokopovich did not idealize the monarchy and did not approve of the idea of restoration. He posed the question of overthrowing Soviet power to the ”will of the Russian people”, but not to acts of emigration and moreover the intervention. Such position was very controversial, since he understood, on the one hand, the illusory intentions of prominent emigrants, and, on the other hand, the impossibility of realizing the ”will of the people”, in the USSR in the 1930s under the circumstances of the totalitarian regime. Reflecting on the goals and objectives of Russian democracy, he proposed orienting himself towards the European line of development, advocated overcoming the political ignorance of the masses, and was a supporter of parliamentary democracy. Analyzing the role of the state in the nation-building process, Sergei Prokopovich pointed out generally the economic factor as the dominant of national progress. First of all, Prokopovich advocated a historical approach to the study of national issues, when the development of the capitalist economy simultaneously with the formation of the state created a political nation (for instance in the USA). As for the independence of the state, firstly, the developed and independent economy was needed, because if it is not present, then political independence becomes a fiction. Considering Russian case, he believed that the resolution of the national question was very difficult because the country was devastated by the Civil war and the revolution, but it was extremely necessary for the future development of Russia to retain the unity of the state language and legal order, the suitable development of industry and railways too. According to his political views, Sergei Prokopovich was a supporter of democracy, political freedom, and a social state. Thus, it can be attributed to the left-centrist wing of the traditional political spectrum.